ERRγ is required for the metabolic maturation of therapeutically functional glucose-responsive β cells - Yoshihara, Eiji (Cell Metab, 2016)
Pancreatic β cells undergo postnatal maturation to achieve maximal glucose-responsive insulin secretion, an energy intensive process. We identify estrogen-related receptor γ (ERRγ) expression as a hallmark of adult, but not neonatal β cells. Postnatal induction of ERRγ drives a transcriptional network activating mitochondrial oxidative phosphorylation, the electron transport chain, and ATP production needed to drive glucose-responsive insulin secretion. Mice deficient in β cell-specific ERRγ expression are glucose intolerant and fail to secrete insulin in response to a glucose challenge. Notably, forced expression of ERRγ in iPSC-derived β-like cells enables glucose-responsive secretion of human insulin in vitro, obviating the need for in vivo ‘maturation’ to achieve functionality. Moreover, these cells rapidly rescue diabetes when transplanted into β cell-deficient mice. These results identify a key role for ERRγ in β cell metabolic maturation, and offer a reproducible, quantifiable and scalable approach for in vitro generation of functional human β cell therapeutics.